Multiple paternity in the Black Caiman (Melanosuchus niger) population in the Anavilhanas National Park, Brazilian Amazonia - Muniz, Fábio L.; Silveira, Ronis da; Campos, Zilca M.S.; Magnusson, William Ernest; Hrbek, Tomas; Farias, Izeni P. (Amphibia Reptilia, 2011)
The formation of dominance hierarchies in which the female mates with a large dominant male is common among crocodilians. However, there is the possibility of polyandry, in which females mate with multiple partners during a single breeding season and generate offspring with multiple paternity. In the present study, eight pairs of heterologous primers developed for Alligator mississippiensis and Caiman latirostris were used to determine whether multiple paternity exists in the Black Caiman, Melanosuchus niger. For such, we analyzed 34 Black Caiman offspring from the Anavilhanas Archipelago in the Negro River (state of Amazonas, Brazil). The specimens came from six groups, each containing five or six hatchlings. Paternity exclusion and genetic identity indices were calculated to test the robustness of the microsatellite loci. Simple allele counts and maximum likelihood estimation of family clusters were used to determine the likelihood of occurrence of multiple paternity. Among the eight loci tested, five were effective at determining paternity, with paternity exclusion values close to 1.0 (QC = 0.92) and genetic identity values close to zero (IC < 0.01). Using the simple allele count, six cases of multiple paternity were detected and confirmed in three hatchling groups by four different microsatellite loci. However, maximum likelihood analysis indicated multiple paternity in all the groups analyzed, with five family clusters identified in one hatchling group alone. Considering that this species is listed according to IUCN as Lower Risk/Conservation Dependent, our results have direct conservation implications. Multiple paternity increases effective population size by maintaining genetic variation, and thus could be an important mechanism to maintain genetic diversity in isolated local populations. © 2011 Brill Academic Publishers.
Keywords: Allele; Breeding Season; Cluster Analysis; Conservation Genetics; Crocodilian; Estimation Method; Genetic Differentiation; Genetic Marker; Heterogeneity; Mathematical Analysis; Paternity; Polyandry; Population Structure; Risk Factor; Amazonas; Rio Negro [south America]; Alligator; Alligator Mississippiensis; Alligatorinae; Caiman Latirostris; Crocodylidae (all Crocodiles); Melanosuchus Niger